Climate Change Impacts on Public Finances Around the World - Lint Barrage (CESifo GmbH, 2024)
This article reviews a rapidly growing literature on how climatic risks and events affect public finances around the world. This literature includes empirical evaluations of how past climatic events have affected fiscal outcomes, empirical and model-based assessments of how climatic risks affect public borrowing costs, and macro-fiscal-climate models that investigate the policy and welfare implications of fiscal climate risks. This article highlights five stylized facts that emerge from this literature and points to important knowledge gaps for future research. Key findings include the facts that (i) the fiscal costs of climatic risks are economically significant overall, (ii) lower-income and credit-constrained regions are especially vulnerable and poorly insured against growing climatic fiscal risks, but that (iii) fiscal policy responses to climatic risks can mitigate their economic impacts substantially.
Keywords: Q54; H20; H50; H60; H70; H84; 330; climate change; fiscal costs; public budgets; sovereign debt; natural disasters; climate adaptation; social cost of carbon; integrated assessment